MACEDONIAN AGRICULTURAL CAPITAL MARKET AND SUPPORTING MECHANISMS: AN OVERVIEW - Simonovska, Ana; Martinovska Stojcheska, Aleksandra; Petrovska Mitrevska, Biljana; Buzharovska, Daniela; Gjosevski, Dragan; Kotevska, Ana (Faculty of Agricultural Sciences and Food - Skopje, 2019)
The Macedonian agricultural capital market is not efficient enough, although there have been some improvements due to the established supporting mechanisms. This paper aims to identify current gaps between agricultural financial services’ and mechanisms’ supply and demand on the agricultural capital market. In this regard, literature and other available secondary sources have been reviewed. Additionally, focused discussions with different stakeholders in the agricultural capital market were conducted, including representatives from the capital demand side (farmers and their associations), and supply side (banks, saving houses, and their associations), as well as supporting institutions and intermediaries (government institutions and donor projects that work towards improvement of farmers’ access to finance in the country). Crediting is one of the key drivers of agricultural and rural development. There are other external financial sources that should be considered, which could contribute in improved capital flow to the agricultural sector. The results revealed critical segments in the agricultural capital market based on the mismatches between the supply and demand for capital and supporting mechanisms, and suggest directions for further improvements of this market. The findings may serve as a baseline for future policy settings and enhancement of a more efficient development of the agricultural capital market in the country.
Keywords: Agriculture, capital demand, capital supply, supporting mechanisms.